Fusarium sp., novo patógeno para Agraulis Vanillae e seu uso no controle biológico - Mueller, Guilherme Henrique (2024)
Biological control or biocontrol, offers alternative methods to manage populations of unwanted organisms besides the use of chemical pesticides. This approach can be applied in various ways, utilizing different control agents. As the organic market grows and new legislation seeks more ecological practices, biocontrol methods are developing alongside the increasing demand. Biocontrol proves particularly useful in pest control, including for caterpillars and moths, which can inflict damage ranging from 20% to 100% on cultivated crops. Microorganisms like bacteria, viruses, and fungi serve as interesting control agents due to their diverse genetic makeup and the possibility of using them independently or in combination with other treatments. This study specifically investigated fungi as potential control agents, particularly due to their versatility and ability to be applied directly on the insect's cuticle, eliminating the need for ingestion. An exploration led to the isolation of a pathogen identified as Fusarium sp. from a larva of Agraulis vanillae (a pest of passion fruit cultivation, Passiflora edulis). This filamentous fungus is known for producing toxic metabolites. To review fungi infectious to Agraulis vanillae, a study was designed to identify fungi causing infection in both A. vanillae and Dione juno (the main caterpillar pest of passion fruit). The results confirmed the effectiveness of three previously mentioned species: Akanthomyces lecanii, Cordyceps tenuipes, and Beauveria bassiana, with Fusarium sp. being the fourth identified pathogen. A second test assessed the pathogen's ability to cause mortality in larvae. Ephestia kuehniella Zeller, a moth known for damaging stored products, served as a model organism. The test involved applying a commercial treatment based on conidia of the fungus Beauveria bassiana to larvae. Additionally, four other treatments were prepared using the Fusarium sp. isolate at different concentrations (100%, 50%, 25%, and 10%). The larvae were observed for sixteen days and monitored for mortality. The results demonstrated the efficacy of Fusarium sp. as a new pathogen, suggesting its potential as a future biological control agent.